Strengthening Core Public Health Capacity Based on the Implementation of the International Health Regulations (IHR) (2005): Chinese Lessons - Bin Liu; Yan Sun; Qian Dong; Zongjiu Zhang; Liang Zhang (Kerman University of Medical Sciences, 2015)
As an international legal instrument, the International Health Regulations (IHR) is internationally binding in 196 countries, especially in all the member states of the World Health Organization (WHO). The IHR aims to prevent, protect against, control, and respond to the international spread of disease and aims to cut out unnecessary interruptions to traffic and trade. To meet IHR requirements, countries need to improve capacity construction by developing, strengthening, and maintaining core response capacities for public health risk and Public Health Emergency of International Concern (PHEIC). In addition, all the related core capacity requirements should be met before June 15, 2012. If not, then the deadline can be extended until 2016 upon request by countries. China has promoted the implementation of the IHR comprehensively, continuingly strengthening the core public health capacity and advancing in core public health emergency capacity building, points of entry capacity building, as well as risk prevention and control of biological events (infectious diseases, zoonotic diseases, and food safety), radiological, nuclear, and chemical events, and other catastrophic events. With significant progress in core capacity building, China has dealt with many public health emergencies successfully, ensuring that its core public health capacity has met the IHR requirements, which was reported to WHO in June 2014. This article describes the steps, measures, and related experiences in the implementation of IHR in China.